Prediksi Tingkat Produksi Panen Buah Jeruk Siam Dengan Metode Regresi Linear Sederhana - Ridwan, Ridwan; Istikoma, Istikoma; Surya, Rizki Surtiyan (Journal of Information System and Technology (JOINT), 2025)
The production of Siam oranges in Sambas Regency has experienced fluctuations, with the highest peak production recorded in 2019 at 123,739 tons, but declining to 88,119 tons in 2023 based on data from the Department of Food Crops and Horticulture of West Kalimantan Province. Additionally, the highest harvest production in 2019 reached 123,739 tons, while in 2021, the lowest production was recorded at 51,691 tons. This decline was largely caused by heavy rainfall and floods that damaged agricultural land. The simple linear regression method produced a regression equation indicating a significant relationship between harvested area (independent variable) and orange production (dependent variable). The results of the analysis using simple linear regression calculations produced a total RMSE value of 17321.364 for 18 sub-districts. This demonstrates that the regression model is effective in predicting orange production in Sambas Regency, considering historical data and the harvested area from 18 sub-districts. This model is expected to assist in planning and decision-making regarding orange production in the future.